THE CHALLENGE OF SURVIVAL OF PATIENTS WITH METASTATIC DE NOVO BREAST CANCER - Leite, Fernanda Perez Magnani; Fernandes, Gisele Aparecida; Fernandes, Allan Alves; Curado, Maria Paula; Sanches, Solanges Moraes; Makdissi, Fabiana Baroni Alves (Mastology, 2021)
Introduction: Breast cancer is the most common cancer in women worldwide, whose treatment is increasingly effective with survival above 90% in initial tumors, while it ranges from 20% to 40.8% in metastatic tumors. However, metastatic breast cancer persists and the survival of these women and treatments remain a challenge for oncology. Objective: To analyze the prognostic factors associated with the survival of patients with metastatic de novo breast cancer. Material and Methods: This is a retrospective cohort of women with stage IV (metastatic) breast cancer, conducted from January 1, 2000 to 31 December 2012, treated at the AC Camargo Cancer Center. The overall 5-year survival (OS) by using the Kaplan– Meier product-limit estimator and the differences between the curves and Cox multiple regression by using log-Rank method were observed. Results: Out of 265 patients analyzed, 182 (68.7 %) were alive at the end of the follow-up. The 5-year survival rate was 29.9%. There was a significant difference in survival rates, according to the categorized age (≤50 years, 51–70 years, and ≥71 years; p<0.046), primary breast tumor surgery (mastectomy and quadrantectomy; p<0.001), exclusive hormone therapy or multimodal treatment (p<0.001), chemotherapy when used in conjunction with radiotherapy, hormone therapy, target therapy, or surgery (p<0.088), treatment initiation period 2000–2005 and 2006–2012 (p<0.004), education, where the greater the school degree, the greater the survival (p<0.001), and luminal tumors (p<0.003). In multiple regression, surgery (p=0.001), chemotherapy (p=0.038), hormone therapy (p<0.001), luminal tumors (p=0.03), having HER2 tumor and using target therapy (p=0.001) and have been treated in the period from 2006 to 2012 (p=0.043) remained as predictive factors for a better prognosis. Conclusion: Patients undergoing resection of the primary tumor had longer survival and better prognosis.